2021
DOI: 10.3390/molecules26092554
|View full text |Cite
|
Sign up to set email alerts
|

Keratin Scaffolds Containing Casomorphin Stimulate Macrophage Infiltration and Accelerate Full-Thickness Cutaneous Wound Healing in Diabetic Mice

Abstract: Impaired wound healing is a major medical challenge, especially in diabetics. Over the centuries, the main goal of tissue engineering and regenerative medicine has been to invent biomaterials that accelerate the wound healing process. In this context, keratin-derived biomaterial is a promising candidate due to its biocompatibility and biodegradability. In this study, we evaluated an insoluble fraction of keratin containing casomorphin as a wound dressing in a full-thickness surgical skin wound model in mice (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…It should be mentioned that lots of studies describe the application of a soluble fraction of keratin as a wound dressing [3,91,92]. However, in the literature, we can find only a few studies that described the insoluble fractions of keratins in wound treatment [7,10,93]. Moreover, the basic wound dressing can be modified with antimicrobial compounds, such as silver nanoparticles (AgNP), antibiotics, or other substances, that can improve the recovery of injured tissues and prevent secondary infection [10,23].…”
Section: Biomedical Propertied Of Keratin Biomaterialsmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be mentioned that lots of studies describe the application of a soluble fraction of keratin as a wound dressing [3,91,92]. However, in the literature, we can find only a few studies that described the insoluble fractions of keratins in wound treatment [7,10,93]. Moreover, the basic wound dressing can be modified with antimicrobial compounds, such as silver nanoparticles (AgNP), antibiotics, or other substances, that can improve the recovery of injured tissues and prevent secondary infection [10,23].…”
Section: Biomedical Propertied Of Keratin Biomaterialsmentioning
confidence: 99%
“…In a subsequent study, Konop et al [93] modified keratin biomaterial (base dressing FKDP) with opioid peptide-casomorphin and examined in vitro and in vivo in diabetic mice model of full-thickness wound model. They showed that casomorphin slowly releases from the wound dressing.…”
Section: Diabetic Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…DWs are hard to repair and tend to become chronic or stalled. The wound bed microenvironment of a chronic or halted wound differs significantly from that of an acute or healing wound, with the high inflammatory intermediaries and proteases levels (8, 9). These wounds will still be in the inflammatory phase, marked by a constant influx of neutrophils and the production of cytotoxic enzymes, reactive oxygen species (ROS), and inflammatory mediators that cause tissue damage.…”
Section: Introductionmentioning
confidence: 99%
“…Added to this is the trend of increased life expectancy, and hence comorbidity, which is accompanied by a growing prevalence of chronic trophic ulcers of various etiologies that are becoming an acute clinical problem [4][5][6]. Despite the constantly increasing number of drugs and methods used to treat wounds, the problem of effective regeneration has not yet been resolved [5][6][7][8][9][10][11][12]. The results of meta-analyses and systematic reviews of the effectiveness of different agents and methods used to treat wounds demonstrate the lack of a uniform and effective approach, as well as a limited choice of drugs for use in wound treatment [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%